A visible-light photoactivatable di-nuclear PtIV triazolato azido complex. Issue 75 (2nd September 2019) - Yao, Kezi; Bertran, Arnau; Howarth, Alison; Goicoechea, Jose M.; Hare, Samuel M.; Rees, Nicholas H.; Foroozandeh, Mohammadali; Bowen, Alice M.; Farrer, Nicola J.
Abstract : A novel Pt IV triazolato azido complex[3]-[N1, N3] has been synthesised via a strain-promoted double-click reaction (SPDC) between a Pt IV azido complex (1 ) and the Sondheimer diyne (2 ). Abstract : A novel Pt IV triazolato azido complex[3]-[N1, N3] has been synthesised via a strain-promoted double-click reaction (SPDC) between a Pt IV azido complex (1 ) and the Sondheimer diyne (2 ). Photoactivation of[3]-[N1, N3] with visible light (452 nm) in the presence of 5′-guanosine monophosphate (5′-GMP) produced both Pt IV and Pt II 5′-GMP species; EPR spectroscopy confirmed the production of both azidyl and hydroxyl radicals. Spin-trapping of photogenerated radicals – particularly hydroxyl radicals – was significantly reduced in the presence of 5′-GMP.